A RELATIONSHIP BETWEEN PROBLEM SOLVING ABILITY AND STUDENTS’ MATHEMATICAL THINKING - Nita Delima (Jurnal Infinity, 2017)
This research have a purpose to know is there an influence of problem solving abilty to students mathematical thinking, and to know how strong problem solving ability affect students mathematical thinking. This research used descriptive quantitative method, which a population is all of students that taking discrete mathematics courses both in department of Information Systems and department of mathematics education. Based on the results of data analysis showed that there are an influence of problem solving ability  to students mathematical thinking either at department of mathematics education or at department of information systems. In this study, it was found that the influence of problem solving ability to students mathematical thinking which take place at mathematics education department is stonger than at information system department. This is because, at mathematics education department, problem-solving activities more often performed in courses than at department of information system. Almost 75% of existing courses in department of mathematics education involve problem solving to the objective of courses, meanwhile, in the department of information systems, there are only 10% of these courses. As a result, mathematics education department student’s are better trained in problem solving than information system department students. So, to improve students’ mathematical thinking, its would be better, at fisrtly enhance the problem solving ability.